ANALISIS SWOT SEBAGAI STRATEGI PENGEMBANGAN SDM (STUDI PADA KARYAWAN UD. REMBULAN PRINTING) - Angga Surya Permana; Muhammad Alkirom Wildan (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study is a qualitative research by exploring both primary and secondary data. Its used direct interviews to the owner of UD. Rembulan Printing and the five people have had appointed to be informants. The results showed that there are 4 strategies to improve the employees performance. Growth strategy (SO) It means that the interpersonal relationships can help the harmonize relationships between employees so that they comfortable and last long in the company. The good services and knowledge sharing can maintain the good relationships with consumers and suppliers (of raw materials). Diversification Strategy (WO) The good recruitment and chancing for fresh graduates who’s expert in financial reporting and good administration. Good relationships between employees can provide motivation and solutions for employees who want to get out of the company. Influencing and providing the best advice to prevent employees for leaving the company. Differentiation Strategy (ST) Management and the employees must be a harmonize relationships for maintaining human resources who experts in printing. And Defensive Strategy (WT) It means the management must improve the quality of human resources.